Novel chromosome-encoded CTX-M-78 β-lactamase from a Kluyvera georgiana clinical isolate as a putative origin of CTX-M-25 subgroup - Rodríguez, María Margarita (2010)
While TEM- and SHV-derived extended-spectrum β-lactamases (ESBLs) arose by point mutations in genes encoding broad-spectrum variants that were extensively disseminated into mobile elements, CTX-M β-lactamases are derived from natural (chromosomal) counterparts that already have oxyimino-cephalosporinase activity.